The motivations and criteria to publish scientific articles - Oliveira, Mariana Paranhos de; Sousa, Rodrigo Silva Caxias de (Informação em Pauta, 2020)
Analyse the informational behaviour of the researchers from PPGGO - UFRGS focused on the criteria and motivations for publishing articles in scientific journals. The study shows a mixed, qualitative-quantitative research, with the application of a questionnaire with the researchers from PPGGO. It lays down criteria for the search, selection and use of information for publication purposes. It lists the most used journals for publications by researchers of the field. It concludes that both the criteria that condition the search for information in relation to the choice of the scientific journal in which to publish the article and what is taken into account in the selection of scientific channels are mainly based on the impact factor of the journal, in the CAPES Qualis table and in the journal's theme. It also stresses the importance of international journals, especially those written in English. It observes as to the motivations for publication of articles that the most important items deal with the academic recognition coming from the publication, the possibility of being cited by other authors and the subject being of their interest and focus.